Efficacy of Prophylactic Tranexamic Acid in Preventing Postpartum Hemorrhage among Preeclamptic Patients Undergoing Cesarean Section - Warda Arshad, Tayyaba Nusrat Ali, Muhammad Awais ur Rehman, Shaista Qurban, Aqsa Akram, Ayesha Khalid (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Morbidity and mortality worldwide, accounting for nearly one-fourth of maternal deaths,bparticularly in low- and middle-income countries.